Thyroid abnormalities in paediatric patients with vitiligo: retrospective study - Kartal, Demet; Borlu, Murat; Çınar, Salih Levent; Kesikoğlu, Ayten; Utaş, Serap (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : The association between vitiligo and thyroid disease is not fully investigated especially in paediatric patients. Aim : To determine the incidence of vitiligo and thyroid disorders in children. This is the first report from middle Anatolia and the second report from Turkey. Material and methods : A retrospective chart review was performed to examine the presence of thyroid abnormalities in paediatric patients who had been admitted to the dermatology department with vitiligo. Results : A total of 155 paediatric patients, including 80 (52%) male and 75 (48%) female patients were included. The mean age was 8.6 years. Non segmental vitiligo was the most common type of the disease in 140 (90%) reviewed patients, while segmental vitiligo appeared only in 15 (10%) patients. The mean onset of vitiligo was 5.6 ±0.9 years. A family history of vitiligo was found in 14 (9%) children. Thirty-four (22%) patients had thyroid function tests and/or thyroid autoantibody abnormality. All of these patients had non segmental vitiligo. It was statistically significant (p < 0.05) in types of vitiligo and thyroid disease parameters. Conclusions : Our results show that it may be useful to screen thyroid in children with non segmental vitiligo.